Isotope composition of snow сover in the Lake Baikal area - Ju. N. Chizhova; J. Yu. Vasilchuk; K. Yoshikawa; N. A. Budantseva; D. L. Golovanov; O. I. Sorokina; Ju. V. Stanilovskaya; Yu. K. Vasil’chuk (Лëд и снег, 2015)
Deuterium and oxygen‑18 are standard water tracers which are widely used to investigate hydrological processes and to trace the moisture sources. In this study, we collected bulk samples taken from the snow cover in the Baikal region distributed from the city Yakutsk to the Lake Baikal. Ulan-Ude had been chosen as a key site to study the snow cover in more details. It has been shown that during the winter season δ18O values in Ulan-Ude reach −39‰ that is typical for the inland air masses of meridional or western transport. The aim of this study was to describe the spatial variability of concentrations of the isotopes deuterium (2H) and oxygen‑18 (18O) in the snow cover.